Problem of the oldest sentence in Czech - Dittmann, Robert (Bohemica Olomucensia, 2012)
The contribution presents several candidates for the oldest Czech sentence. It attempts to challenge the almost universally accepted primacy of the Leitmeritz inscription from the early 13th century by drawing attention to overlooked alternative candidates.